Demographic influences on employee perceptions of Robotic Process Automation at a South African telecommunications company - Robertson, Shaun (University of the Witwatersrand, Johannesburg, 2023)
This research report investigates the influence of employees’ demographic characteristics on their perceptions of robotic process automation (RPA) in a South African telecommunications company. It uses an exploratory, non- experimental, quantitative research approach and presents and analyses primary data collected through an online survey instrument distributed to a cross-sectional, self-selection sample of employees. The research found that a large majority of employees perceived RPA to be beneficial to themselves and to the business and, were neither for nor against the implementation of RPA, but that they also believed that RPA was not flexible enough to be applied to every business task or process. It was also found that demographics have much less of an influence on employees’ perceptions of RPA than might be expected
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Robotic Process Automation; Perceptions of RPA; Fear of becoming unemployed; Telecommunications; Technology acceptance; UCTD; SDG-9: Industry, innovation and infrastructure